2018
DOI: 10.18311/mvpjms/2018/v5/i1/19735
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Severe Anemia in Children in a Tertiary Care Institute

Abstract: Introduction: The present study was to emphasize the chief causative factors, clinical manifestations, various hematological and morphological types in children with severe anemia, admitted to the pediatric wards of a tertiary care hospital. Objectives: The primary objective was to study clinical profile of severe anemia in children with various risk factor and hematological parameters among children with severe anemia. Methods: This was an observational study conducted in a tertiary health care institute. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 2 publications
7
7
0
Order By: Relevance
“…Male: Female was 1.6:1. These results were in accordance with Sunil Gomber et al 11 , Abhishek Janjale et al 12 , Jasima et al 13 who reported Male: Female as 1.15:1, 1.45:1 & 1.7:1 respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Male: Female was 1.6:1. These results were in accordance with Sunil Gomber et al 11 , Abhishek Janjale et al 12 , Jasima et al 13 who reported Male: Female as 1.15:1, 1.45:1 & 1.7:1 respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Nutritional anemia was reported as commonest cause of anemia in children in this study. These results supported by many other studies especially from developing countries [8,9,14]. WHO estimated that iron deficiency anemia is responsible for 50% of cases of anemia in fewer than 5 children [1].…”
Section: Discussionsupporting
confidence: 78%
“…In study by Janjale et al, incidence of severe anemia was more in <3.5 years age group (50.85%). Male to female ratio was 1.45:1 [7]. As reported by Bharati et al, the most common age group affected with anemia was 12-23 months with prevalence rate of 68.1% followed by 9-11 months (prevalence, 67.2%) and 6-8 months (prevalence, 65.9%) [8].…”
Section: Resultsmentioning
confidence: 62%
“…The Indian studies have consistently shown an association between anemia and under-nutrition [3,[5][6][7][8]. It can be seen that anemia is influenced by socioeconomic, biological, environmental, and nutritional factors.…”
mentioning
confidence: 99%